Economic Losses From Marine Pollution ( sach photocopy) - Ofiara Douglas D.; Seneca Joseph J. (American : Island Press, 2001)
Marine pollution causes significant damage to fisheries and other economically productive uses of the ocean. The value of that damage can be quantified by economists, but the meanings of those valuations and how they are derived are often obscure to noneconomists.
Economic Losses from Marine Pollution brings a fuller understanding of the variety and extent of marine losses and how they are assessed to scientists, lawyers, and environmentalists by systematically identifying and classifying marine losses and relating them to models and methods of economic valuation. The authors use a step-by-step approach to show how economists have used these methods and how they approach the problem of assessing economic damage.
The book begins by describing the importance of economic valuation of marine damages, the history of concern over marine pollution, and the development of economic methodologies to assess damage from it. Following that, the book
considers types of marine pollution and their effects on organisms, ecosystems, and humans, and the corresponding economic effects of those biological impacts
introduces the economic principles and methods needed to understand and to assess economic damages
expresses losses from water quality impairments in terms of economic value
introduces the basic economic techniques that have been developed and used to measure changes in economic value
discusses how to apply those economic techniques, and presents a variety of practical examples
explores limitations and problems that can arise in such applied work.
Keywords: Ô nhiễm nước